The Effect Of Using Task Based Language Teaching In Teaching Speaking Virtually For The Seventh Grade Students Of Methodist-2 Medan - Jessica Tryadi; Sondang Manik; Arsen Nahum Pasaribu (International Journal of Educational Research & Social Sciences, 2021)
The study is intended to see whether using task-based language teaching invirtual classroom is effective in teaching speaking for the seventh grade studentsof SMP Methodist-2 Medan. Asking students to memorize expressions used indialogues is not the key to achieve success in teaching speaking for students.Language learners should be able to communicate not only in the classroompractices but also in the real situations. Creating such situations in an onlineclass are challenging yet essential to help students acquire speaking skills.Task-Based Language Teaching is the way to solve the problem where learnersare provided with chances to learn language by working to complete ameaningful task. The writers want to find out whether using task-basedlanguage teaching (TBLT) in teaching speaking can overcome the challenge andcan make significant effect in teaching speaking English especially when it isconducted on virtual classes. This is an experimental research. Analyzing theeffect of the implementation of using the approach in teaching speaking for theseventh grade students of SMP Methodist-2 Medan is conducted virtually. Theresult of this research is alternative hypothesis (H1) which states that studentswho are taught through task-based language teaching have better speaking skillthan those who are not.